2020
DOI: 10.1155/2020/8758905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Occlusion Chemically Assisted Ablation (MOCA) for Saphenous Vein Insufficiency: A Meta-Analysis of a Randomized Trial

Abstract: Purpose. A previous meta-analysis has conducted nonrandomized trials for mechanochemical ablation (MOCA). Since medium-term follow-up data from randomized clinical trials (RCTs) are becoming available, we chose to perform a meta-analysis of RCTs to assess the efficacy and safety of MOCA for saphenous vein insufficiency. Methods. A systematic search of all RCTs comparing the anatomical success of MOCA for saphenous vein insufficiency to thermal ablation was performed using the PubMed and Cochrane Library databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 19 publications
(30 reference statements)
0
12
1
Order By: Relevance
“…The recurrence rate after SSV surgery has been reported to range from 8.6% to 30%, with better results for concomitant SPJ ligation and SSV stripping. 7,12,13 In addition, follow-up data at more than one year after MOCA of the SSV are lacking, 9,10,14,15 and our results go further than 18 months. Although multiple prospective trials over the last two decades compare MOCA to other endovenous procedures, and OS is no longer a primary choice in many centers, SSV ligation and stripping is not a completely abandoned procedure.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…The recurrence rate after SSV surgery has been reported to range from 8.6% to 30%, with better results for concomitant SPJ ligation and SSV stripping. 7,12,13 In addition, follow-up data at more than one year after MOCA of the SSV are lacking, 9,10,14,15 and our results go further than 18 months. Although multiple prospective trials over the last two decades compare MOCA to other endovenous procedures, and OS is no longer a primary choice in many centers, SSV ligation and stripping is not a completely abandoned procedure.…”
Section: Discussioncontrasting
confidence: 66%
“…In previous studies, one of the major benefits of MOCA reported is the pain intensity reduction during the procedure compared with thermal ablations. 15,17,18 In our study, intraoperative pain could not be evaluated in the OS group because all procedures were performed under regional or general anesthesia, and no comparison could be made between groups. However, our findings confirmed that MOCA is painless on the first postoperative day compared to OS and has a significantly lower procedural time, explaining the shorter time to return to work (MOCA 3.5 ± 2.3 days vs. OS 14.2 ± 3.8 days, p < .0001).…”
Section: Discussionmentioning
confidence: 99%
“…The tumescentless mechanochemical ablation (MOCA) technique has become an alternative treatment modality. Mechanochemical devices (ClariVein, Flebogrif) have been developed to minimize the negative aspects of both endothermal ablation and ultrasound-guided foam sclerotherapy for the treatment of saphenous incompetence, while incorporating the benefits of each [1][2][3][4][5][6]. Treatment with MOCA resulted in less postoperative pain/edema and a faster improvement in the Venous Clinical Severity Score (VCSS) in the short term but more hyperpigmentation compared with radiofrequency ablation (RFA) [7].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, MOCA was associated with a significant reduction in rates of ecchymosis and hematoma formation and postoperative phlebitis and a shorter time to return to work compared with thermal ablation [2,8]. In comparative studies, including the Mechanochemical endovenous Ablation to RADiOf-requeNcy Ablation (MARADONA) study [7], short-term (6-month) outcomes were similar with MOCA and RFA, but there were more anatomical failures between 6 months and 3 years after MOCA than after RFA [5][6][7]. However, compared with RFA, MOCA was associated with a lower incidence of nerve injury, deep vein thrombosis, and skin burns [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation